Automatização de planilha para cálculo da tarifa do transporte público urbano pelo método Leonês - Alves, Helder Vasconcelos (Universidade Federal de São Carlos, 2021)
The demand for the urban public transport system in Brazil has been declining gradually in recent years. Factors, such as the low quality of service provision and the growing value of fares, have kept users away, especially those with lower incomes, from this mode of transportation. The quality of the service provided can be attributed to several factors, from errors in the design of the transport system to poor quality in the roads used by the buses. The high cost of the tariff, on the other hand, is linked, at first, to the increase in the prices of some elements (fuel, taxes, administrative expenses) and, later, to the lack of structure (human, material, tools) in the tariff administration. The calculation methods used by cities for the most part are outdated or obsolete, requiring new ways of calculating the value of tariffs. Thus, the automation of calculation methods means that the competent bodies and designers spend less time on operational demands and can focus on more in-depth analyzes of the costs of the urban public transport system. This study will focus on automating one of these calculation methods, Leonês, proposed by Ferraz in 1999. Such automation will be performed in Microsoft Excel using the software's own programming language, called VBA (Visual Basic for Applications). Finally, the following results were obtained: the final calculation spreadsheet, considerations in the design of the spreadsheet and future ideas for possible improvements in the built program.
Worksheet automation for calculating urban public transport tariffs using the Leonese method
Keywords: Transporte público; Tarifa; Automação; VBA; Ônibus; Método Leonês; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::OPERACOES DE TRANSPORTES; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::PLANEJAMENTO DE TRANSPORTES